2020
DOI: 10.1101/2020.07.29.225599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ciliary protein IFT88 controls post-natal cartilage thickness and influences development of osteoarthritis

Abstract: Mechanical forces are known to drive cellular signalling programmes in cartilage development, health, and disease. Proteins of the primary cilium, implicated in mechanoregulation, control cartilage formation during skeletal development, but their role in post-natal cartilage is unknown. Ift88fl/fl and AggrecanCreERT2 mice were crossed to create a cartilage specific inducible knockout mouse AggrecanCreERT2;Ift88fl/fl. Tibial articular cartilage thickness was assessed, through adolescence and adulthood, by histo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Understanding the complex role of the primary cilium in articular cartilage in vivo is confounded by the effects of cilia loss on skeletal development. Most recently, Coveney et al used the cartilage-specific inducible deletion of IFT88 to remove cilia in mouse joints after skeletal maturity [11]. These studies confirmed a role for the cilium in the mechanosensitive regulation of matrix production, with defects in cartilage formation/maintenance only apparent in regions of the joint subject to higher levels of loading in aged mice [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding the complex role of the primary cilium in articular cartilage in vivo is confounded by the effects of cilia loss on skeletal development. Most recently, Coveney et al used the cartilage-specific inducible deletion of IFT88 to remove cilia in mouse joints after skeletal maturity [11]. These studies confirmed a role for the cilium in the mechanosensitive regulation of matrix production, with defects in cartilage formation/maintenance only apparent in regions of the joint subject to higher levels of loading in aged mice [11].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Coveney et al used the cartilage-specific inducible deletion of IFT88 to remove cilia in mouse joints after skeletal maturity [11]. These studies confirmed a role for the cilium in the mechanosensitive regulation of matrix production, with defects in cartilage formation/maintenance only apparent in regions of the joint subject to higher levels of loading in aged mice [11]. In the current study, loss of pkd1/pkd2 expression did not result in a change in the regulation of matrix gene expression in the absence of strain, but it rather inhibited mechanosensitive matrix gene expression (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together our data establish the cilium as a cellular location for ENPP-1 EV shedding. Consistent with a role in cilia, mammalian ENPP1 loss-of-function manifests signs of ciliopathies, such as accelerated ossification, hearing impairment, altered insulin metabolism and immune response [43][44][45][46].…”
Section: Cilia Produce Evs That Carry Nucleic Acid-binding Proteins Sid-2 Enpp-1 and Mcm-3mentioning
confidence: 89%